Story, past and modernity: The festive cycle of Santiago Apóstol in Río Grande (Atacama, Chile) - Álvarez González, Jaime (2013)
Through participant observation, analysis of sources and comparing stories about the festivity of St. James in the village of Rio Grande, Antofagasta Region, Chile, this article explores the changes and continuities that can be identified in various rites of this Andean community of northern Chile. Considering diverse stories that comprehend different celebrations that are involved in the devotion to the Apostle James, we propose the existence of a “festive cycle”, which lasts around a week. In addition, relevant milestones are recognized so to expose the continuity of tradition, and changes that occur over time, which can be attributed to the advance of modernity within the community of Río Grande.